2018
DOI: 10.24820/ark.5550190.p010.547
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-proliferative activity of novel oxepin-annulated coumarins

Abstract: A series of fused dihydrooxepino[h]-and dihydrooxepino[g]coumarins (7 and 8) were synthesized through allylation, Claisen rearrangement, allylation and ring-closing metathesis (RCM), respectively. All the synthesized compounds were characterized by appropriate spectral analysis. The anti-proliferative activities of compound 5a-c, 6a, 6c, 7a-c and 8a-c were evaluated against human colon cancer (Caco-2), liver cancer (HepG2) and breast cancer (SKBR-3) cell lines using tamoxifen (TAM) as the positive control. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“… 53 Antiviral bioassay data (see Table 1 and Figure 4 ) indicated that most of the compounds demonstrated a dose-dependent inhibition behavior. Based on the U.S. National Cancer Institute (NCI) and GERAN protocol, 54 , 55 the LD 50 values indicate that most tested compounds, especially compound 3b, are safe for healthy cells, while the plaque reduction assay showed that compounds 3b , 4 , and 10b have higher therapeutic indices compared to the other synthesized compounds. In particular, compound 3b exhibited the highest antiviral activity at the given concentrations with percentage of virus reduction reaching 85% at a concentration of 0.25 μmol/ml.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 53 Antiviral bioassay data (see Table 1 and Figure 4 ) indicated that most of the compounds demonstrated a dose-dependent inhibition behavior. Based on the U.S. National Cancer Institute (NCI) and GERAN protocol, 54 , 55 the LD 50 values indicate that most tested compounds, especially compound 3b, are safe for healthy cells, while the plaque reduction assay showed that compounds 3b , 4 , and 10b have higher therapeutic indices compared to the other synthesized compounds. In particular, compound 3b exhibited the highest antiviral activity at the given concentrations with percentage of virus reduction reaching 85% at a concentration of 0.25 μmol/ml.…”
Section: Resultsmentioning
confidence: 99%
“…53 Antiviral bioassay data (see Table 1 and Figure 4) indicated that most of the compounds demonstrated a dosedependent inhibition behavior. Based on the U.S. National Cancer Institute (NCI) and GERAN protocol, 54,55 Synthesis of N-(5-Amino-4-cyano-1H-pyrazol-3-yl)benzamide 4. Method: hydrazine hydrate (0.50 g, 0.01 mol) was added to a solution of N-[2,2-dicyano-1-(alkylsulfanyl)ethenyl]benzamide (3a−c) (0.01 mol) in ethanol (20 mL) in the presence of drops of piperidine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[93] S C H E M E 3 9 Cu-catalyzed synthesis of chloro-functionalized naphto [ marins 186 and evaluated the in vitro antiproliferative activity of the synthesized compounds against cancer cell lines. [10] Allyloxy coumarins are obtained by reaction of the corresponding coumarins with allyl bromide in the presence of a base. The Claisen rearrangement and again allylation produced a mixture of respective regioisomers, which after the purification process, under a ring closure metathesis reaction by Grubbs' first-generation catalyst afforded oxepin-annulated coumarins (Scheme 53).…”
Section: Ruthenium-catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…These compounds were found to have potential uses in pharmaceuticals [4][5][6] and also in polymers. The number of biological properties of these compounds is containing anti-inflammatory, [7][8][9] antiproliferative, [10] antitumor [1] and anticancer, [10] antiplasmodial, [11] antihelminthic activity, [12] antibiotic activity, [13][14][15][16] antiestrogenic, [17] analgesic, [18] antipsychotic, [9,[19][20][21] angiotensin II receptor antagonistic, [22] antioxidant, [23] antimycobacterial, [24] and antiapoptosis. [25] Some of oxepine, benzoxepine, and dibenzoxepine derivatives have been synthesized by Tishchenko-like reaction, [26] Friedel-Crafts acylation reactions, [27] Suzuki coupling, [28] and Catellani reaction.…”
Section: Introductionmentioning
confidence: 99%